Enzyme immobilization: Implementation of nanoparticles and an insight into polystyrene as the contemporary immobilization matrix. (September 2022) - Sharma, Shivam; Gupta, Shubham; Princy,; Arya, Shailendra Kumar; Kaur, Anupreet
Abstract: Enzyme immobilization has plethora of applications in industrial and production activities. This is predominantly because immobilized enzymes have elevated long-term operational stability against pH, temperature, contaminants etc. Besides, these have extended shelf lives and are simpler to handle. Immobilized enzymes have enhanced activity, reclaimable as well as recoverable. Since the traditional techniques for immobilization often lead to decreased enzyme activity, contemporary investigations probing the use of nanoparticles for immobilization have emerged. As the stability of immobilized enzymes depends on its interaction with the carrier, employment of the nanoparticles as carriers seems a plausible option owing to their large surface area to volume ratio. Thus, higher surface energy and improved magnetic properties. Nevertheless, nanoparticles exhibit highly porous and hollow structures. In this article, overview of eminence of incorporating nanoparticles in enzyme immobilization has been delved. Merits include improved thermal stability at temperatures as high up to 80 °C for enzymes like β-Glucosidase, better storage stability as compared to free enzymes over long time periods. For instance, laccase maintains 60% residual activity through 30 days. Reusability of enzymes also increases as immobilized enzymes showed higher residual activity and greater catalysis cycles. 59 consecutive catalysis cycles retaining 100% of initial activity has been reported in case of invertase. Further, an insight into the use of various polymer surfaces for enzyme immobilization procedures as applicable in different domains have also been put forth. Furthermore, the leverages of polystyrene surface for enzyme immobilization include chemical inertness, cheaper than most synthetic polymers, non-toxic and mechanical rigidity makes this as the novel support material. Lastly, different techniques used to immobilize enzymes over polystyrene surfaces have also been reviewed. Highlights: This review article introduces our study on nanoparticles and their use in enzyme immobilization. Different types of nanoparticles can be characterized by multiple number of characterization techniques. Enzymes immobilized with nanoparticles showed greater thermal stability free enzymes. Improved storage stability of immobilized enzymes with better residual activity than free enzymes. Uses of polystyrene surfaces as choice of support for immobilization.